PENERAPAN MODEL PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PADA MATA PELAJARAN FIKIH SISWA KELAS VIII MTS HIDAYATUL ISLAM LANGKAT - Lilis Rusmiati; Diani Syahfitri; Yusuf Abdullah (Jurnal Iqtirahaat, 2023)
The problem in this research is the low grades of students so that there is a need to increase learning outcomes. Data analysis used in this research is test and non-test. Based on the results of this study, the inquiry learning model in improving student learning outcomes was classified as good with the results of the recapitulation research. The average score of students in cycle I was 59% and cycle II was 100%, while the PKK score of students after applying the jigsaw learning model was 75%, increasing to 88. %. Thus it can be concluded that the inquiry learning model in improving student learning outcomes in science subjects is quite good. As the end of this study concluded that the inquiry learning model is very well used in an effort to improve students' critical thinking skills because the inquiry learning model involves all students so that students become active.